Komposisi dan Kelimpahan Makrozoobentos pada habitat padang lamun di Desa Wakambangura, Buton Tengah - Ilham Antariksa Tasabaramo; Riska Riska; Arman Pariakan; Hasan Eldin Adimu (Faculty of Science and Technology University Ibrahimy, 2024)
The role of seagrass beds as permanent habitat for marine biota, including macrozoobenthos. Macrozoobenthos are sessile biota that live at the bottom or in sediment and attach to plants. The aim of this research is to determine the composition and abundance of macrozoobenthos in Wakambangura Village waters. The macrozoobenthos collection method uses a 100 m line transect towards the sea using a shovel with a cross-sectional area of 30x40 cm. The research locations are spread across 3 stations, Station 1 Weta Beach, Station 2 Mbelabela Beach and Station 3 residential areas. As a result of the research, 24 macrozoobenthos species were found consisting of 5 classes, namely 15 species from the Gastropoda class, 5 species from the Bivalvia class, 1 Asteroides species, 1 Ophiuroidea species and 2 species from the Crustacea class. The Gastropoda class dominates with a macrozoobenthos composition value of 70.59%. The highest abundance of macrozoobenthos was found at station 2 with an abundance value of 292 Ind/m2, then the lowest abundance was found at station 3 with an abundance value of 108 Ind/m2. The highest species abundance was found in the species Cerithium rostratum with an abundance of 108 Ind/m2.